Formation and annealing of vacancy-P complexes in proton-irradiated germanium. (November 2015) - Elsayed, M.; Arutyunov, N.Yu.; Krause-Rehberg, R.; Oganesyan, G.A.; Kozlovski, V.V.
Graphical abstract: Abstract: We have used positron annihilation spectroscopy to study the formation and annealing of defects in germanium irradiated with 15 MeV protons under different doses at 300 K. The samples were n -type Ge ([P] = 2 × 10 17  cm −3 ). Deep and shallow positron states were observed, which were attributed to the vacancy complexes as well as to the negative ion defects. The complex defect is established to involve a vacancy and a phosphorous atom. Isochronal annealing of the irradiated material was carried out over the temperature range 300–740 K. The positron lifetime in the temperature interval 35–300 K was measured after each isochronal annealing step. Two salient temperature stages of annealing were found. The first stage ranging from 400 to 500 K was attributed to the annealing of the vacancy complexes. Vacancy clusters involving two vacancies begin to appear at 420 K in the course of the isochronal annealing, whereas further increase of the annealing temperature up to 520 K gives rise to the formation of clusters of about 3 vacancies. The second annealing stage is over the temperature range of 550–650 K, which is ascribed to annealing of vacancy clusters. The model of negative-ion-type positron traps was used for describing the results of the positron lifetime measurements related to the shallow positron traps. These defects disappear within the annealing temperatures range 500–600 K. After annealing of the irradiated material at 740 K, the average positron lifetime is almost the same as that of the non-irradiated Ge material.